IDENTIFIKASI KINERJA DAN KESENJANGAN STAKEHOLDER DALAM PELESTARIAN ELANG JAWA [Spizaetus bartelsi] - Kuswandono .; Arzyana Sunkar; Lilik Budi Prasetyo (Department of Forest Resources Conservation and Ecotourism - IPB University, 2010)
This approach is quite different from existing conservation actions, which are site based and fragmented. Research was conducted since December 2009 until February 2010 in Gunung Gede Pangrango National Park (GGPNP), Telaga Warna Nature Reserve and its surrounding forested areas. The objectives of this study were to: 1) identify relevant stakeholders in Javan Hawk-eagle conservation, 2) identify regulation related to Javan Hawk-eagle conservation, 3) analyze stakeholder performance related to Javan Hawk-eagle conservation, 4) analyze the gaps in Javan Hawk-eagle conservation (gap in normative performance and implemented performance, gap between groups of stakeholders within protected areas and outside area, and gap performance among stakeholders within protected areas, and 5) identify factors causing the gaps. Primary data were collected using indepth interview and field observation. Stakeholders were identified through snowball method. Secondary data were collected through reference study. Data analysis were conducted using spatial analysis, stakeholder identification and analysis, content analysis and gap analysis. Research results recognized two conservation management approaches: 1) species level, and 2) habitat level. These approaches would effectively conserve the existing fragmented and less protected forest blocks as well as boost the participation and synergism of many stakeholders. Further, by using this approach, a gap in conservation management among local conservation agencies would also be discussed for the benefit of the Javan Hawk-eagle’s conservation in particular and for biodiversity in general. Keywords: conservation, stakeholders, performance, gap analysis, Javan Hawk-eagle